Variation of surface properties of ceramic and composite nanostructures and their measurements by a novel approach using perichromic dyes - Tayel, Amr Mohamed (AUC Knowledge Fountain, 2015)
TiO2 as a model photocatalyst is gaining great interest due to good activity, stability, low toxicity and cost-effectiveness. The rapid recombination between the photogenerated electrons and the holes on the TiO2 surface can be diminished by using carbon-TiO2 composites, especially Graphene (G) and Graphene Oxide (GO), which improve the photocatalytic activity of TiO2 and stability under UV-visible light illumination. The determination of surface properties including surface acidity, polarity and surface area of photocatalysts allows the control and enhancement in the photocatalytic efficiency. This study aims at investigating the surface properties of TiO2-G and TiO2-GO nanocomposites using independent techniques, correlating these surface properties and photocatalytic activity and studying the effect of particle size and the amount of G and GO on these surface properties. TiO2 nanoparticles of different sizes were prepared using sol-gel methodology and varying the rate of hydrolysis of the TiO2 precursor. The as-prepared TiO2 nanoparticles were used to prepare TiO2-G and TiO2-GO nanocomposites by mixing followed by sonication and stirring. The variables in the prepared nanocomposites were the percentage of the added G or GO together with the different TiO2 particle size. Characterization of the formed nanocomposites and the blank samples was performed by using different techniques. The surface acidity was measured using perichromic dyes and NH3-TPD; both measurements are independent. Surface polarity and polarizability were investigated using perichromic dyes to study their impact on the photocatalytic activity. Textural properties were investigated by measuring the surface area and average pore diameter. The structural characteristics of the samples were evaluated using FTIR, Raman and XRD. DRS-UV was employed to measure the band gap energy change with the addition of G or GO. The photocatalytic degradation of methylene blue (MB) dye, as a model water pollutant, was used to evaluate the photocatalytic activity of the samples. The characterization results indicated that two methods of preparation gave two average sizes of 436 ±59 nm and 251 ±32 nm for the samples denoted TL and TS which corresponds to large particle size TiO2 and small particle size TiO2, respectively. Addition of G and GO affected the structure, surface properties and photocatalytic activity of the sample. The results for the photocatalytic activity of the prepared samples, exhibited superior activity over the unmodified TiO2 and the rate enhancement ranged from 9.2 to 69.2% for TS, and 18.8 to 237.5% for TL, showing the clear advantage of using nanocomposites as photocatalysts for pollutants. Photocatalytic activity of the samples is dependent on many factors such as surface acidity, surface area and, to a much lesser extent, the change in band gap energy and the overall effect is a complex combination of all these factors. The formation of Ti-O-C chemical bonds in the samples is evidenced by the Raman results and the addition of G or GO has no effect on the crystal structure of the sample as shown in XRD results. The increase in overall surface acidity in most samples is believed to be primarily due to Brønsted acidity as Lewis acidity is generally lower than the blank in most samples. However, possible stacking of G and GO at higher concentrations resulted in the decrease in overall acidity with the increase in G or GO contents in some of the samples. Surface polarizability, which measures primarily the van der Waals surface interactions, increased with the increase in G content as would be expected due to the hydrophobic nature of G. Further investigations are needed, however, to extend the use of perichromic probes for determination of surface polarizability of solid surfaces. The overall surface acidity of the TL containing samples is generally higher than the TS samples due to higher degree of cross-linking. In conclusion, TiO2-G and TiO2-GO nanocomposites prepared by mixing and sonication were studied for the effects of changing TiO2 particle size, and of the presence and amount of G and GO. It was found that smaller particle size and the presence of G or GO improved the photocatalytic activity of the samples through the change in sample surface properties. Increasing the amount of G or GO in the samples led to limitations in the enhancement of catalytic activity. This is believed to be primarily due to possible blockage of the photocatalytic active sites on the surface of TiO2.